Nexus between Economic Phenomena and Growth Rate of Fishery Sector in Nigeria - Sadiq, S. M.; Singh, I. P.; Ahmad, M. M. (Indonesian Journal of Agricultural Research, 2021)
Time series data that spanned from 1981-2019 sourced from CBN, FAO, and UNCTAD data banks were used to determine the growth of fishery sector in Nigeria. The obtained data was analyzed using the two-step methodology of Engel and Granger, Granger causality, and the impulse response function. The result showed evidence of co-integration between fishery GDP growth rate and the economic phenomena. Also, the GDP growth rate of the sector is efficient as it established a long-run equilibrium but the slow pace at which it corrects the distortion in its equilibrium makes the state of the efficiency to be a weak one. Furthermore, the fishery’s GDP growth rate is affected by high inflationary trend, red-tapism, and poor credit utilization. Empirical evidences showed that unexpected local shocks on the economic phenomenon will have a transitory effect on FGDP growth rate, thus will die-out over time. It was observed that the effect of the internal mechanism on the growth rate is passive while the external system effect is active on the growth rate. Therefore, the study recommends the need for policy strengthening by the concerned stakeholders viz: tiding of inflationary trend, red-tapism, and ineffective credit utilization, thus enhancing the growth of the sector.